Exploring the Nonlinearities between Capital Structure and Interactions of Competition, Efficiency, and Stability - Insights from African Banking Sector - Mauto, Respect Kudzai; Marire, Junious; Khumalo, Sibanisezwe A.; Malumisa, Sambulo (International Journal of Economics and Financial Issues, 2026)
This study investigates the nonlinear effects of the joint interaction of competition, efficiency, and stability on bank capital structure in African commercial banks, using the capital asset ratio (CAR) and a composite institutional index (CESINDEX). The analysis draws on a balanced panel of 792 bank-year observations from 66 commercial banks across 12 African countries. Baseline estimates are obtained using the Fixed Effects Model (FEM), while robustness and endogeneity concerns are addressed using the two-step System Generalized Method of Moments (GMM). Quantile regression is further employed to examine distributional heterogeneity across different capitalization levels. The results reveal a statistically significant inverted U-shaped relationship between CESINDEX and CAR, indicating the existence of an optimal institutional threshold, with turning points at CESINDEX = 0.0923 and CAR = 0.301, beyond which further institutional intensity weakens capitalization. Competition, efficiency, and return on assets exert negative effects on CAR, whereas stability and CESINDEX positively influence capital buffers, while macroeconomic variables show no significant impact. Quantile results indicate that marginal effects vary across the CAR distribution, with stronger effects at middle and upper quantiles. These findings underscore the importance of nonlinear, distribution-sensitive institutional dynamics for effective capital regulation and bank resilience in African banking systems.